Mucinous Rectal Adenocarcinoma Is Associated with a Poor Response to Neoadjuvant Chemoradiotherapy: A Systematic Review and Meta-analysis. Issue 12 (December 2016) - McCawley, Niamh; Clancy, Cillian; O'Neill, Brian D. P.; Deasy, Joseph; McNamara, Deborah A.; Burke, John P.
Abstract : BACKGROUND: Mucinous adenocarcinoma represents a potentially poor prognostic subgroup of rectal cancer. A consensus on the effect of mucinous cancer on outcomes following neoadjuvant chemoradiotherapy and curative resection for rectal cancer has not been reached. OBJECTIVE: The aim of the current study is to use meta-analytical techniques to assess the association between mucinous histology and response to neoadjuvant chemoradiotherapy in rectal cancer. DATA SOURCES: A comprehensive literature search of PubMed, Embase, and The Cochrane Library was performed. STUDY SELECTION: All studies examining the effect of mucinous histology on chemotherapeutic response in rectal cancer were included. INTERVENTIONS: No direct interventions were performed. MAIN OUTCOME MEASURES: Outcomes of mucinous rectal adenocarcinoma were compared with nonmucinous tumors by using random-effects methods to analyze data. Data are presented as ORs with 95% CIs. The main outcomes measured were the rates of pathological complete response, tumor and nodal downstaging, positive resection margin rate, local recurrence, and overall mortality. RESULTS: Eight comparative series describing outcomes in 1724 patients were identified, 241 had mucinous tumors (14%). Mucinous tumors had a reduced rate of pathological complete response (OR, 0.078; 95% CI, 0.015–0.397; p = 0.002) and tumor downstaging (OR, 0.318; 95% CI, 0.185–0.547; p < 0.001) following neoadjuvant chemoradiotherapy with an increased rate of positive resection margin (OR, 5.018; 95% CI, 3.224–7.810; p < 0.001) and poorer overall survival (OR, 1.526; 95% CI, 1.060–2.198; p = 0.023) following resection. Mucin expression did not significantly affect nodal downstaging (OR, 0.706; 95% CI, 0.295–1.693; p = 0.435) or local recurrence (OR, 1.856; 95% CI, 0.933–3.693; p = 0.078). There was no across-study heterogeneity for any end point. LIMITATIONS: Most studies were retrospectively designed, and there were variations in patient populations and duration of follow-up. CONCLUSIONS: Mucinous rectal adenocarcinoma represents a biomarker for poor response to preoperative chemoradiotherapy and is an adverse prognostic indicator.